The Impact Of Merger And Acquisition (M&A) In Malaysian Banking Industry: An Examination - Abdul Fatah, Faizal Shah (2008)
The objective of this study is to identify and analyse the impact of merger and acquisition (M&A) in the Malaysian banking industry.